Continuous flow synthesis of zeolite FAU in an oscillatory baffled reactor. Issue 2 (9th February 2020) - Ramirez Mendoza, Heidy; Valdez Lancinha Pereira, Mafalda; Van Gerven, Tom; Lutz, Cécile
Abstract: In this work, we report, for the first time, the continuous flow synthesis of zeolite NaX successfully accomplished in a pilot‐scale (up to 100 L/h) continuous oscillatory baffled reactor (COBR). The continuous synthesis was achieved by combining the seed‐assisted method, in‐line mixing of reactants at high temperature and COBR. The use of a COBR not only allowed the same residence time as the batch system, but also a controlled temperature profile, thanks to the plug flow behavior and effective heat transfer. A stable continuous operation was maintained during 5 hours owing to an effective mixing, preventing any hydrodynamic failure caused by the sedimentation of zeolite crystals. The results showed that zeolite NaX was obtained after 99 minutes and crystals between 0.6 and 0.7 μm were observed by scanning electron microscopy. The effect of frequency and amplitude on crystal properties was assessed. Sampling at three points along the COBR allowed the study of steady states of the zeolite concentration in temporal and spatial domains.